La nature et les ruines : anciennes présences humaines dans le récit climatique de science‑fiction - Rémi Auvertin (ReS Futurae, 2023)
European modernity and romanticism have made the human ruin a symbol of the passage of time and the fall of civilizations. The motif persists durably in contemporary culture and in the archaeological imagination of most people. This imaginary is well present in science fiction, and in particular in narratives marked by climatic upheavals: if nature itself makes a clean sweep, certain traces of human occupation escape complete destruction. Whether placed in a specific environmental framework (rising waters, global warming, snow) or in a more global civilizational narrative, the climatic ruin can be observed as an architectural discourse, as a visual and aesthetic object or as a narratological device. Built at the intersection of different cultural models (the climatic or archaeological imaginary, the post-apocalyptic city, the dead city), these everyday landscapes, reclaimed by nature, crystallize the anxiety of a non‑return. Conversely, they affirm the need to adapt to new environmental conditions and to build new ways of life.Our reflection, influenced by archaeology, focuses on two complementary media, the novel and the comic strip, whose comparison highlights the stability of the motif but also the tension between realism and universalism.